Respostas
respondido por:
10
Olá!
Temos os seguintes dados:
a - b = 1
ab = 1
a² + b² = ?
Solução:
Temos um produto notável, (a - b)², resolvendo-o, temos:
(a - b)² = a² + b² - 2ab
Sabemos que: a - b = 1 e ab = 1, então:
(a - b)² = a² + b² - 2*ab
(1)² = a² + b² - 2*1
1 = a² + b² - 2
1 + 2 = a² + b²
3 = a² + b²
a² + b² = 3
Temos os seguintes dados:
a - b = 1
ab = 1
a² + b² = ?
Solução:
Temos um produto notável, (a - b)², resolvendo-o, temos:
(a - b)² = a² + b² - 2ab
Sabemos que: a - b = 1 e ab = 1, então:
(a - b)² = a² + b² - 2*ab
(1)² = a² + b² - 2*1
1 = a² + b² - 2
1 + 2 = a² + b²
3 = a² + b²
a² + b² = 3
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás